Differential expression and regulation of FASLG by miR-5195/miR-3941 in age-related hearing loss - Jeongmin Lee; Junseo Jung; Hyunsook Kang; Kyeongjin Park; Jong Bin Lee; Seongjun Choi (PLoS ONE, 2025)
Presbycusis, or age-related hearing loss (ARHL), is a progressive condition that involves a steady decline in auditory function, primarily caused by the physiological alterations that occur with aging. This disorder arises from the combined effect of multiple interconnected factors that progressively affect the auditory system over time. Genome-wide association studies (GWAS) and transcriptomic analyses in human populations are valuable approaches for identifying potential genes associated with ARHL. This research seeks to assess the potential of protective drugs or strategies for treating ARHL by analyzing target gene-miRNA interactions identified in human blood and associated with presbycusis. We performed RNA sequencing to analyze the transcriptomes of peripheral blood leukocytes from ARHL patients. To identify genes associated with ARHL, the RNA-sequencing data from the peripheral blood leukocytes were compared and further validated by real-time polymerase chain reaction (RT-qPCR) using whole blood samples from the same ARHL patients. To explore the involvement of target genes and microRNAs (miRNAs) in ARHL, we examined miRNA expression patterns using RT-qPCR and reporter gene assays. We found that four genes were up-expressed in ARHL serum: Fas Ligand (FASLG), Neural Cell Adhesion Molecule 1 (NCAM1), Nectin Cell Adhesion Molecule 1 (NECTIN1), Macrophage Receptor with Collagenous Structure (MARCO). The up-expressed FASLG is associated with cell apoptosis and aging. Additionally, we showed that miR‑5195 and miR-3941 regulated FASLG expression in House Ear Institute-Organ of Corti 1 (HEI-OC-1) and HeLa cells via targeting of FASLG using luciferase reporter assays. Finally, the over-expression of the FASLG gene may be associated with the development of ARHL, and the inhibitory role of miR-5195 and miR-3941 could be a key factor in the prevention or protection against ARHL.